Systematic review and meta-analysis evaluating the effectiveness of home safety interventions (education and provision of safety equipment) for child injury prevention. (7th October 2012) - Kendrick, D; Wynn, P; Young, B; Mason-Jones, A; Ilyas, N; Achana, F; Cooper, N.; Hubbard, S; Sutton, A; Smith, S; Mulvaney, C; Watson, M; et al.
Abstract : Background: Injuries are the leading cause of childhood death in industrialised countries with steep social gradients in morbidity and mortality. Most injuries in pre-school children occur at home, however there is little meta-analytic evidence that home safety interventions (HSI) reduce injury rates, improve safety practices or impact on injury inequalities. Aims/Objectives/Purpose: To investigate effectiveness of HSI in increasing home safety practices and reducing child injury rates and whether the effect varied by social group. Methods: Bibliographic databases, relevant websites, conference proceedings, bibliographies of relevant studies, and previously published reviews were searched. Results/Outcome: 54 studies were included in at least one meta-analysis. HSI were effective in promoting safe hot tap water temperatures (OR 1.41, 95% CI 1.07 to 1.86), functional smoke alarms (OR 1.81, 95% CI 1.30 to 2.52), fire escape plans (OR 2.01, 95% CI 1, 45 to 2.77), storing medicines (OR 1.53, 95% CI 1.27 to 1.84) and cleaning products (OR 1.55, 95% CI 1.22 to 1.96) out of reach, having syrup of ipecac (OR 3.34, 95% CI 1.50 to 7.44) and poison control centre numbers accessible (OR 3.30, 95% CI 1.70 to 6.39) and fitted stair gates (OR 1.61, 95% CI 1.19 to 2.17). HSI may reduce injury rates especially when delivered at home (IRR 0.75, 95% CI 0.62 to 0.91). There was no consistent evidence that HSI were less effective in those at greater risk of injury. Significance/Contribution to the Field: HSI are effective in increasing a range of safety practices and may reduce injury rates without widening existing inequalities.